Analyzing Public Transportation Plans to Addressing Traffic Congestions in Developing Countries - Hussaen Ali Hasan Kahachi (Iraqi Journal of Architecture and Planning, 2019)
Traffic congestions is one of the main problems for many cities especially in newly urbanizing countries worldwide. The issue of traffic congestions has major impact not only on the planning of the city, but also on many aspects such as residence overall well-being. Governments often try to address this issue through a number of initiatives, most important of which is promoting public transport in order to reduce the dependency on private cars in the city. This research analyzed state-led public transportation initiatives impact on addressing traffic congestion in developing countries through a case study of the Greater Cairo Region in Egypt. The research specifically focused on two state-led public transportation programs, namely the Great Cairo Transport Authority (CTA) program to improve the existing public transport services in GCR and the GCR underground metro program during the 1990s to early 2010s. The research found that although these programs were successful in limiting the increase of privately owned cars and taxies in GCR, they did not decrease traffic congestions due to a number of issues including malpractice, political and administrative corruption, and rapid population growth and increased population densities that almost doubled in the period from early 1990s to early 2010s.